If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 63 = c + -21 + 2c Reorder the terms: 63 = -21 + c + 2c Combine like terms: c + 2c = 3c 63 = -21 + 3c Solving 63 = -21 + 3c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-3c' to each side of the equation. 63 + -3c = -21 + 3c + -3c Combine like terms: 3c + -3c = 0 63 + -3c = -21 + 0 63 + -3c = -21 Add '-63' to each side of the equation. 63 + -63 + -3c = -21 + -63 Combine like terms: 63 + -63 = 0 0 + -3c = -21 + -63 -3c = -21 + -63 Combine like terms: -21 + -63 = -84 -3c = -84 Divide each side by '-3'. c = 28 Simplifying c = 28
| 3/6=/8 | | 16+x=42 | | 3.29-0.223= | | 4t^2-20t-60=0 | | 2sin(30+x)=3cosx | | 2+p=2 | | 5n-6=7 | | ln(x)+ln(1.1675x)=5.28 | | 5x-6=93-6x | | 5t+4=11 | | -14=x/2 | | (3x-9)(2x-2)= | | 4.500+60v=50(100+v) | | 4(13-y)+2y=36 | | -42+14x=4y | | 3y+2x-7+12-6x+4y=56-45x+2y | | (c+2)=5(c+1)-7 | | n-3=1 | | -5v=-5 | | 32+(-16)+(-12)= | | 2(c+2)=5(x+1)-7 | | -3x^4+5x^3-2x^2+9=0 | | y=3x^5-4x^2+2 | | 3/5n=6 | | 3y-8+6x= | | (3x^2-2x+4)-(-5x^2+3x-8)= | | 11v-12/v-5 | | 5x+7y=19fory | | 5=5x-27 | | 3z-5(100-3x)=400 | | X+25=3x+27 | | -16=4+x |